Poisoning by toxic plants and fungi. (March 2020) - Singh, Manjeet; Routledge, Philip A.
Abstract: Some species of plants and fungi can cause severe toxicity generally after the accidental or deliberate ingestion of plant or fungal materials. Cardiotoxicity, neurotoxicity, hepatotoxicity and renal toxicity are some of the more serious consequences. Advice from the local poisons information service is valuable in managing suspected poisoning from plants and fungi.